The relationship between palate depth and facial profile analysis: Hubungan kedalaman palatum dengan analisis profil wajah - Nahusona, Donald R.; Maulana, Lalu Novan (Makassar Dental Journal PDGI Makassar, 2025)
Facial profile characteristics are associated with the morphology of a person's palate so that several categories of palate depth are obtained, but research and information regarding the relationship between palate depth and facial profile is still very little so it is deemed necessary to conduct research on this matter. This study discusses the relationship between palate depth and fa-cial profile analysis using subjects who are preclinical students of the Faculty of Dentistry Unhas. This type of research is analytic descriptive observational with cross-sectional design by simple stratified random sampling. The subjects were examined using in-traoral and extraoral radiographs. The characteristics of the palate were shallow (2.41%), medium (16.87%), and deep (80.72%). While according to the type of facial profile; concave 2.41%, straight 18.07%, and convex (79.52%). Pearson chi-square corre-lation statistical test obtained p>0.05. It was concluded that deep palate and convex facial profile type dominated the categories studied, and there was no relationship between palate depth and facial profile analysis.